Automated Verification Methodology of Security Events Based on Heuristic Analysis. (27th September 2015) - Song, Jungsuk; Lee, Younsu; Kim, Kyuil; Kim, Seokhun; Kim, SooKyun; Choi, Sang-Soo
We present an automated verification methodology of the security events, that is, IDS alerts, based on heuristic analysis. The proposed verification methodology aims to automatically identify real cyberattacks from the security events and filter out false positive, so that the security analyst is able to conduct security monitoring and response more effectively. For the proposed verification methodology, we used the 1, 528, 730, 667 security events that were obtained from Science and Technology Security Center (S&T-SEC). We then extracted the core security events that were caused by the real cyberattacks. Among the core security events, we selected the top 20 types of the security events in the number of the real attacks that they raised. By analyzing the top 20 types of the security events, we discovered essential elements and optional elements for using in the automated verification of the security events. The evaluation results showed that the proposed verification methodology could contribute to the reduction (about 67%) of the meaningless security events. Furthermore, we demonstrated that the proposed verification methodology contributed to the detection of 140 true negatives that were not identified by the security analyst and the total accuracy of the proposed verification methodology was 96.1%.